IMPLEMENTATION OF SAFE DROWNING SANCTIONS FOREIGN FISHING VESSELS IN FISHERIES CRIMES - Bambang Irianto (SYNTIFIC, 2023)
Background. Fishing activities carried out by a certain country or foreign fishing vessels in waters that are not in its jurisdiction without permission from the country that has jurisdiction. The purpose was to determine the sanctions against perpetrators of fisheries crimes in Indonesia and the implementation of sanctions for the sinking of foreign fishing vessels that commit fishing crimes without permission in Indonesia. Research Method. This research was type of normative legal research, doctrinal research because this research is conducted or aimed only at written regulations and other legal materials. Normative legal research is also referred to as literature review because this research is mostly done on secondary data in the library and document studies. Findings. The implementation of the sanction of sinking foreign fishing vessels against perpetrators of fisheries crimes is carried out through court decisions or due to caught red-handed foreign fishing vessels confiscated based on Court decisions can be sunk by the Prosecutor as the executor or executor of the judge's decision. In the case of being caught red-handed, it must be based on sufficient preliminary evidence or preliminary evidence to suspect the existence of fisheries crime by foreign fishing vessels. Conclusion. Sanctions against perpetrators of fisheries crime are heavy sanctions, because they are cumulative, namely imprisonment and fines imposed at the same time against the perpetrators of criminal acts. In addition to criminal sanctions, perpetrators can also be subject to administrative sanctions in the form of warnings, license suspension and up to license revocation.